Agriculture in Brazil's Midwest region: Limitations and future challenges to development - César Nunes de Castro (Institute for Applied Economic Research (ipea), 2015)
Among the economic activities in Brazil's Midwest region, agriculture has an important role in the regional economy, with the aim of this study to evaluate the recent situation of regional agriculture in order to identify constraints and opportunities for development and discuss actions that may contribute to the expansion of regional production. A region that increased its participation in national agricultural gross domestic product (GDP), from 7.4% in 1970 to 19.5% in 2009, demonstrated in the recent past that it has favorable conditions for agricultural economically profitable exploitation. Several factors, however, are often mentioned as potential barriers to the development of agriculture in the region, including environmental issues, disability logistics, technological backwardness, lack of credit, lack of technical assistance, among others. For this competitiveness to continue and possibly even increase, many investments are needed, especially in improving the transportation infrastructure for transport of produce to consumer centers.
Keywords: Q1; Q10; 330; agriculture; livestock; Midwest region; development